METHODICAL BASES OF TEACHING HIGHER MATHEMATICS BY THE ELECTRONIC TEXTBOOK - Sidorenko-Nickolashina, О.Л. (Journal of Information Technologies in Education (ITE), 2011)
This work examines principle of systematization, structurization and visualization of the academic material in the higher mathematics by means of structurally-logical charts. Bases of teaching method of students is offered by the electronic textbook, which contains the text of the academic material, package of proper it structurally-logical charts of different level of working out in detail, and also some tasks of the professional orientation.